Secure integration of IoT and Cloud Computing - Stergiou, Christos; Psannis, Kostas E.; Kim, Byung-Gyu; Gupta, Brij (Future generation computer systems, 2018)
Mobile Cloud Computing is a new technology which refers to an infrastructure where both data storage and data processing operate outside of the mobile device. Another recent technology is Internet of Things. Internet of Things is a new technology which is growing rapidly in the field of telecommunications. More specifically, IoT related with wireless telecommunications. The main goal of the interaction and cooperation between things and objects which sent through the wireless networks is to fulfill the objective set to them as a combined entity. In addition, there is a rapid development of both technologies, Cloud Computing and Internet of Things, regard the field of wireless communications. In this paper, we present a survey of IoT and Cloud Computing with a focus on the security issues of both technologies. Specifically, we combine the two aforementioned technologies (i.e Cloud Computing and IoT) in order to examine the common features, and in order to discover the benefits of their integration. Concluding, we present the contribution of Cloud Computing to the IoT technology. Thus, it shows how the Cloud Computing technology improves the function of the IoT. Finally, we survey the security challenges of the integration of IoT and Cloud Computing. •Presentation of IoT and Cloud technologies which focus on security issues.•Integration benefits of Internet of Things and Cloud Computing technologies.•Part of AES presented for improvement of security issue, resulting from integration.•Contribution of AES and RSA algorithms in the integration of IoT and Cloud technologies.